Electrodeposited zinc oxide nanostructures with adsorbed natural dyes for photovoltaic applications - Klochko, N.P.; Khrypunov, G.S.; Myagchenko, Y.O.; Melnychuk, E.E.; Kopach, V.R.; Klepikova, K.S.; Lyubov, V.M.; Kopach, A.V. (Functional Materials, 2012)
We report on a cost-effective alternative synthetic method for creation of ZnO-based natural-dye sensitized solar cells (DSSC). ZnO arrays were electrodeposited on transparent fluorine doped tin oxide covered glass cathodes in aqueous electrolytes in three-electrode cell under potentiostatic conditions and under pulse plating modes with rectangular impulses of cathode potential. Then ZnO layers were dye-sensitized by a freshly prepared blackcurrant juice. The studies of structure by XRD-method, surface morphology by atomic force microscopy and optical properties by spectrophotometry have demonstrated the promise of ZnO arrays electrochemically grown in the rectangular pulse mode for creation of natural-dye sensitized DSSC.